Wakaf Tunai dan Pemberdayaan Ekonomi Masyarakat - Said, Salmah; Amiruddin, Andi Muhammad Ali (Al-Mashrafiyah: Jurnal Ekonomi, Keuangan, dan Perbankan Syariah, 2019)
Waqf is one of muamalah activities that has spiritual, social and economic dimensions. Traditionally, waqf has only been interpreted as giving in the form of immovable property such as land and buildings whose designation is limited to the construction of houses of worship and education (schools). However, in fact movable endowments such as cash waqf (money) has long been practiced by Muslims such as in the Umayyad and Abbasid dynasties, only not as popular as land or building endowments. At present, along with the development of public understanding of the practice of Islamic philanthropy, endowments, especially cash waqf, are directed towards the development and empowerment of the economy, for the sake of fulfilling society economic welfare. Keywords: Cash Waqf, Muamalah Activities, Society Economic Welfare. Wakaf merupakan salah satu kegiatan muamalah yang memiliki dimensi spiritual, sosial, dan ekonomi. Secara tradisional, selama ini wakaf hanya dimaknai sebagai pemberian dalam bentuk barang tidak bergerak seperti tanah dan bangunan yang peruntukannya terbatas pada pembangunan rumah ibadah dan pendidikan. Namun, sebenarnya wakaf barang bergerak seperti wakaf tunai (uang) telah lama dipraktikkan oleh umat Islam seperti di masa dinasti Umayah dan Abbasiyah, hanya tidak sepopuler wakaf tanah ataupun bangunan. Saat ini, seiring perkembangan pemahaman masyarakat tentang praktik filantropi Islam, wakaf terutama wakaf tunai diarahkan bagi pengembangan dan pemberdayaan ekonomi, untuk sebesar-besarnya peningkatan kesejahteraan ekonomi umat. Kata Kunci: Wakaf Tunai, Kegiatan Muamalah, Kesejahteraan Ekonomi Umat